Proses Pengembalian Kendaraan Bermotor Sebagai Barang Bukti dalam Perkara Pidana di Kejaksaan Negeri Batam - Athiifah Hanum; Atiikah Hanum; Muhammad Fajar Hidayat (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The process of returning a motorized vehicle as evidence in a criminal case at the Batam District Prosecutor's Office. This research aims to describe and analyze the process of returning motorized vehicles, starting from confiscation, storage, to returning them to their legal owners. The research method used is the normative legal method with secondary data, including primary legal materials (legislation), secondary legal materials (books and journals regarding the return of evidence), and tertiary legal materials (articles and internet news) and through interviews with officers. Batam District Prosecutor's Office. The research results show that the process for returning motorized vehicles at the Batam District Prosecutor's Office has been clearly regulated in statutory regulations and the Attorney General's Circular Letter. This process generally runs smoothly and orderly. However, in some cases, there are obstacles encountered in the process of returning motorized vehicles, such as a lack of complete vehicle documents, as well as a lack of complete data such as the vehicle owner's cellphone number which can no longer be contacted. The Batam District Prosecutor's Office has made efforts to overcome these obstacles.